(m - 2) - 5 = 8 - 2(m - 4)
The objective is to isolate m (get m by itself). By PEMDAS, the first step is to get rid of the parentheses. Apply the distributive property - a(b + c) = ab + ac.
(m - 2) - 5 = 8 - 2(m - 4)
m - 2 - 5 = 8 - 2m + 8
Combine like terms (constants) on both sides.
m - 2 - 5 = 8 - 2m + 8
m - 7 = 16 - 2m
Add 7 to both sides to get rid of the constant on the left side of the equation.
m - 7 = 16 - 2m
m = 23 - 2m
Add 2m to both sides to get rid of the variable term on the right side of the equation.
3m = 23
Divide both sides by 3 to isolate m.
3m = 23
m =
![7(2)/(3)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/1mrmkvxuc7trzskdq75jisfwjb58tk1j47.png)
Answer:
m =
![7(2)/(3)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/1mrmkvxuc7trzskdq75jisfwjb58tk1j47.png)